Preparation and characterization of tungsten carbide from carbon of palm kernel shell for remidiation of dichlorodifluoromethane (CFC-12) - 409517 Nurul Aqmar Siam; Abdul Rahim Yacob (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2008